Fire endurance and corrosion resistance of nano-modified cement mortars exposed to elevated temperatures - Chousidis, Nikolaos; Constantinides, Georgios (My University, 2023)
In this study, the influence of high temperature on corrosion resistance of steel rebars and the mechanical strength of nano-modified mortars is investigated. Two (2) different mixtures were prepared and tested in the lab; mortars containing 0.2 wt% multi-walled carbon nanotubes (MWCNTs) and mortars without nanomaterials for comparison reasons. The specimens were heated in a furnace up to 800οC for 1 h. Destructive and non-destructive tests were used to evaluate the fire resistance and durability performance of cementitious materials. In particular, the corrosion protection provided by nanomaterials was investigated using electrochemical and mass loss measurements on reinforcing steel, whilst strength tests of mortars were also carried out to evaluate their mechanical behavior after exposure in elevated temperatures. SEM and XRD techniques were used to analyze the surface and microstructure of the steel bars and mortars. The results showed, that the CNT addition slightly improves the strength and durability of mortars exposed to high temperatures as compared with the plain OPC mortar. At the same time, the corrosion resistance of steel rebars was enhanced using carbon nanotubes in mortars after exposure to high temperatures.
Keywords: Cement mortars; Nanomaterials; Carbon nanotubes; Corrosion resistance; Mechanical properties